2016
DOI: 10.1111/cdep.12208
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Neuroprotective Care in Neonatal Intensive Care Units and Preterm Infant Development: Insights From the Neonatal Adequate Care for Quality of Life Study

Abstract: During their stay in a neonatal intensive care unit (NICU), preterm infants are exposed to adverse stressful experiences that deplete their resources and often result in problematic functioning and developmental outcomes. The impact of specific developmental care practices (e.g., kangaroo care) on preterm infants has been researched extensively. Moreover, the dissemination of knowledge about developmental care has facilitated broader neuroprotective care (NC) that combines different kinds of developmental care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…However, these survivors still experience increased morbidity and mortality rates because of prematurity (Lasiuk, Comeau, & Newburn-Cook, 2013). The majority of preterm infants must stay in neonatal intensive care units (NICUs) to receive life-saving care in their early days of life; in the NICU, the infants experience numerous stressors, such as excessive noise and lights, painful stimuli, and prolonged separation from their parents (Montirosso, Tronick, & Borgatti, 2017;Newnham, Inder, & Milgrom, 2009). A growing body of evidence has shown that the quality of life of preterm infants is threatened by potential developmental and health issues, such as brain damage, delays in motor and mental development, and behavioural problems (Jarjour, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these survivors still experience increased morbidity and mortality rates because of prematurity (Lasiuk, Comeau, & Newburn-Cook, 2013). The majority of preterm infants must stay in neonatal intensive care units (NICUs) to receive life-saving care in their early days of life; in the NICU, the infants experience numerous stressors, such as excessive noise and lights, painful stimuli, and prolonged separation from their parents (Montirosso, Tronick, & Borgatti, 2017;Newnham, Inder, & Milgrom, 2009). A growing body of evidence has shown that the quality of life of preterm infants is threatened by potential developmental and health issues, such as brain damage, delays in motor and mental development, and behavioural problems (Jarjour, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As for clinical implications, the present results are particularly intriguing in the context of previous works suggesting that early interventions during the NICU stay might have an impact on the neurodevelopment of preterm infants [52,53]. For example, Als and colleagues [54] have demonstrated that a specific and comprehensive program of developmental care in the NICU (i.e., the Newborn Individualized Developmental Care and Assessment Program, NID-CAP) is associated with increased coherence between frontal and occipital brain regions, higher anisotropy in left internal capsule with a trend for frontal white matter.…”
Section: Discussionmentioning
confidence: 72%
“…These programs focus on a healing environment, on partnership with families, on proper NB positioning, on sleep protection, on reducing stress and pain, on skin protection and on optimizing total nutrition. Interventions to promote stability such as NB organization in nests, facilitated containment, delicate handling, and comfortable positioning should be incorporated into routine care (36)(37) . The prevention and treatment of pain is a human right.…”
Section: Discussionmentioning
confidence: 99%